(untitled) (AYUSHDHARA, 2016)
Qarabadin (Unani pharmacopoeias) have a rich armamentarium of natural drugs, consisting of mostly herbs but also materials of animal, mineral and marine origin. There are over 2,000 species of plants in the Unani Materia Medica of which many species of plants occurring in India found a place. In addition to treatises concerned just with medicinal substances, books were also composed listing recipes in which a number of medical substances would be compounded. Such medical formularies (Qarabadin) were usually arranged into Chapter concerned with a particular type of remedy, such as laxatives or salves or eye remedies, and some were prepared specifically for use in hospitals. There are many collections of different formularies in Qarabadins have been written by Unani physicians. The first true medical formulary ever created was al-Aqrabadhin written in Arabic by Sabur ibn Sahl (d. 869). The book included medical recipes stating the methods and techniques of compounding remedies, their pharmacological actions, the dosages, and the means of administration. The formulas are organized by the type of preparation to which they belong - i.e. tablets, powders, ointments, electuaries or syrups. Sabur’s formulary-type compendium is unique in its organization and purposely written as a guidebook for pharmacists, whether for use in their own private drugstores or in hospital pharmacies. This article describes the contribution of eminent Unani Physicians, scholars, scientists and authors in development of Pharmacy.